(untitled) (Journal of the College of Languages (JCL), 2009)
English, like any other language, has a number of such discourse markers including well, yes, surely, on the contrary, so and nevertheless. They are lexical items or grammatical forms typically serve to relate one utterance to another in discourse.Discourse markers are considered as cues or signals for the reader or the hearer that make cohesion and coherence, In fact, these markers are found in various grammatical forms such as interjections, linking adverbials, greetings and farewells….etc. Discourse markers. Play a very important role, not only in conversation, but in written text as well.